2019
DOI: 10.1111/codi.14724
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CT colonography in the preoperative staging of colon cancer: a prospective study of 217 patients

Abstract: Aim The purpose of the present study was to evaluate the accuracy of computed tomography colonography (CTC) in the preoperative localization and TN staging of colon cancer. CTC can be an effective technique for preoperative evaluation of colon cancer and could facilitate the selection of high‐risk patients who may benefit from neoadjuvant chemotherapy. Method This was a prospective observational study conducted at a single tertiary‐care centre. It involved 217 patients (225 tumours) who had colon cancer and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…A more recent study by Maupoey Ibanez et al. (15) showed an 87% accuracy of differentiating T1/T2 from T3/T4 stage (κ = 0.7) and an N-stage accuracy of 69% (κ = 0.37). The current main use of CTC is as an alternative to conventional colonoscopy in cases of obstructive colorectal cancer (3).…”
Section: Discussionmentioning
confidence: 94%
“…A more recent study by Maupoey Ibanez et al. (15) showed an 87% accuracy of differentiating T1/T2 from T3/T4 stage (κ = 0.7) and an N-stage accuracy of 69% (κ = 0.37). The current main use of CTC is as an alternative to conventional colonoscopy in cases of obstructive colorectal cancer (3).…”
Section: Discussionmentioning
confidence: 94%
“…13,15,25,28 Ibanez et al found that it could accurately differentiate tumours confined to the colon wall (T1/T2) from higher staged tumours (T3/T4). 11,12,19,20,28 In locally advanced tumours, there may be a role for neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Five studies used the term 'obstructing tumours' but failed to define it. [19][20][21][22][23] Three studies used the term 'obstructive tumour' as defined as incomplete colonoscopy or where the colonoscope failed to observe the proximal colon. [24][25][26] Two studies used 'stenosing' cancers, tumours or masses in their description, but both failed to define this term.…”
Section: Study Terminology and Definitions Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography (CT) is a widely used method for reporting colon cancer. It is currently the national standard, with a sufficient ability to distinguish between small and advanced colon tumors (1,2). Upon suspicion of colon cancer, patients will be offered a CT scan with the purpose of locating possible distant metastases and assess the characteristics of the tumor (3).…”
Section: Introductionmentioning
confidence: 99%